1985
DOI: 10.1542/peds.75.5.908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Furosemide on the Clinical Course of Transient Tachypnea of the Newborn

Abstract: The effect of furosemide on the course of transient tachypnea of the newborn was evaluated in a controlled, prospective study. Fifty infants with transient tachypnea of the newborn were randomly assigned to control or treatment groups. Those in the treatment group were given furosemide, 2 mg/kg orally, at the time of diagnosis followed by 1 mg/kg 12 hours later if the symptoms persisted. Infants in the control group received a placebo. Compared with infants in the control group, the furosemide-treated group de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our study also showed that role of Furosemide in TTN management is insignificant. Similar results were shown by Wiswell and colleagues on 50 infants, 21 and by Karabayir et al, in 2006. 22 Group-C received both IV Furosemide and nebulized Salbutamol.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also showed that role of Furosemide in TTN management is insignificant. Similar results were shown by Wiswell and colleagues on 50 infants, 21 and by Karabayir et al, in 2006. 22 Group-C received both IV Furosemide and nebulized Salbutamol.…”
Section: Discussionsupporting
confidence: 89%
“…15 A study carried out by Wiswell et al on oral use of Furosemide has not shown any benefit in either the severity or duration of the illness or length of hospitalization. 16 In addition, oxygen supplementation was reduced in those patients with restricted fluids compared to standard fluid therapy. 17 Moresco et al compared different treatment modalities for TTN like inhaled epinephrine and salbutamol, fluid restriction, non-invasive ventilation and Furosemide and found that hospital stays for the Salbutamol Group were significantly shorter than other interventions.…”
Section: Discussionmentioning
confidence: 99%